2020
DOI: 10.3390/biomedicines8110465
|View full text |Cite
|
Sign up to set email alerts
|

FAM188B Expression Is Critical for Cell Growth via FOXM1 Regulation in Lung Cancer

Abstract: Although family with sequence similarity 188 member B (FAM188B) is known to be a member of a novel putative deubiquitinase family, its biological role has not been fully elucidated. Here, we demonstrate the oncogenic function of FAM188B via regulation of forkhead box M1 (FOXM1), another oncogenic transcription factor, in lung cancer cells. FAM188B knockdown induced the inhibition of cell growth along with the downregulation of mRNA and protein levels of FOXM1. FAM188B knockdown also resulted in downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, FAM188B knockdown inhibited cell aggregate formation in all three cell lines with an increase in dead cells stained by PI and shown in red ( Figure 2 C). Although we used si-FAM188B RNA that has been described in our previous report [ 14 ], we also used other si-FAM188B RNAs to avoid off-target effects. As shown in Figure S2 , all three si-FAM188B RNAs reduced cell aggregate formation in the suspension culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, FAM188B knockdown inhibited cell aggregate formation in all three cell lines with an increase in dead cells stained by PI and shown in red ( Figure 2 C). Although we used si-FAM188B RNA that has been described in our previous report [ 14 ], we also used other si-FAM188B RNAs to avoid off-target effects. As shown in Figure S2 , all three si-FAM188B RNAs reduced cell aggregate formation in the suspension culture.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FAM188B knockdown decreased cell growth in the 3D culture condition, which mimics in vivo conditions ( Figure 4 E). FAM188B knockdown decreased levels of Survivin, which is an anti-apoptotic protein that plays a critical role in anoikis resistance [ 14 ]. Recently, we reported that FAM188B knockdown decreased levels of FOXM1, an oncogenic transcription factor, with an increase in its ubiquitination in A549 cells [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 18S rRNA was used as an internal control gene for several target genes (Supplementary Table S5). Amplification was carried out (n = 3) on a LC480 real-time PCR system (Roche, Basel, Switzerland) as described in a previous report [33].…”
Section: Quantitative Reverse Transcription Pcrmentioning
confidence: 99%